Genome-wide identification of the TGA genes in common bean (Phaseolus vulgaris) and revealing their functions in response to Fusarium oxysporum f. sp. phaseoli infection - Liu, Yu; Huang, Yuning; Li, Zhao; Feng, Ming; Ge, Weide; Zhong, Chao; Xue, Renfeng (Frontiers in Genetics, 2023)
use they might be used to manage disease. As a crucial regulator, TGA-binding transcription factor (TGA) is engaged in the defense mechanism of plants against pathogens. The role of TGA regulators in common bean in response to Fop infection, however, has not been documented. Hence, we performed genome-wide identified and characterized eight TGA genes in common bean. In this study, eight PvTGA genes were distributed on six chromosomes and classified into four subgroups. The PvTGA genes have the same conserved bZIP and DOG1 domains, but there are specific sequence structures in different PvTGAs. Phylogenetic and synteny analysis explained that PvTGA gene has a close genetic relationship with legume TGAs and that PvTGA03 and PvTGA05 may play an important role in evolution. Transcriptome data explained that expression levels of PvTGA genes showed diversity in different tissues. After Fop inoculation, the expression levels of PvTGA03 and PvTGA07 were significantly different between resistant and susceptible genotypes. Under SA treatment, the expression levels of PvTGA03, PvTGA04, PvTGA06, PvTGA07 and PvTGA08 were significantly different. These results imply that PvTGA03 and PvTGA07 play key roles in SA-mediated resistance to Fusarium wilt. Together, these findings advance knowledge of the PvTGA gene family in common bean and will help future studies aimed at reducing Fusarium wilt.